1994
DOI: 10.1163/22941932-90001378
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ebony and Streaked Woods

Abstract: Samples of 175 Diospyros species were examined with 27 containing some ebonised wood which was rarely uniformly jet black. Ebony is commonly composed of a series of axial and alternating black and paler streaks, often in characteristic patterns as in D. celebica. Large amounts of black non-structural deposits first appear in vessels, then fibres, and the origin of these materials could not be found. Deposits were absent from the axial and ray parenchyma of the paler streaks. Crystals were present in some speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The deposits first become evident in the vessels of the sapwood adjacent to the streaks but deposits in the rays of the streaks of some Diospyros spp. are absent (Hillis & Soenardi 1994;Hillis 1995). The thin coloured streaks in some species cannot be associated with signs of injury.…”
Section: Introductionmentioning
confidence: 99%
“…The deposits first become evident in the vessels of the sapwood adjacent to the streaks but deposits in the rays of the streaks of some Diospyros spp. are absent (Hillis & Soenardi 1994;Hillis 1995). The thin coloured streaks in some species cannot be associated with signs of injury.…”
Section: Introductionmentioning
confidence: 99%
“…Previous phytochemical studies on this plant have resulted in the isolation and characterization of new coumarins, namely crassiflorone, diosfeboside A and diosfeboside B [8,9]. In continuation of this study, we investigated the chloroform and ethyl acetate extracts of the stems of D. crassiflora, which led to the isolation of three new norbergenin derivatives (1)(2)(3), along with ten known compounds (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). This paper deals with the structural elucidation of the new compounds, as well as the preliminary evaluation of the antioxidant properties of some isolates, especially of their ability to protect PC12 cells against hydrogen peroxide induced injury.…”
mentioning
confidence: 99%
“…Both bark and leaves are used to treat wounds [3,4]. D. crassiflora produced a valuable timber known as black ebony and, in the past few years, its over exploitation drove this species into a risk of extinction [1,5]. Recently, it was reported that extracts of leaves of D. crassiflora possessed antifungal, antimycobacterial and antigonorrhoeal activities [6,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The two most notable examples found are “ebony” and “rosewood”. The term “ebony” has been long referred to the genus Diospyros [ 30 ], which comprises over 700 species of which it is estimated that only about 30 yield timber of commercial interest [ 39 ]. However, the term is frequently used for dark-colored heavy and hard timbers belonging to other genera too [ 40 ].…”
Section: Resultsmentioning
confidence: 99%